Thermoreversible gelation of poly(vinylidene fluoride-co- chlorotrifluoroethylene): Structure, morphology, thermodynamics, and theoretical prediction - Yadav P.J.P.; Maiti B.; Ghorai B.K.; Sastry P.U.; Patra A.K.; Aswal V.K.; Maiti P. (My University, 2025)
Thermoreversible gelation of a copolymer, poly(vinylidene fluoride-co-chlorotrifluoroethylene), has been studied in a series of aromatic diesters (phthalates) with varying aliphatic chain length, n. The gelation rate gradually increases with increasing n, but no gelation occurs in dioctyl phthalate (n = 8), giving rise to a solvent dependency. Structures of gels and dried gels have been studied through X-ray diffraction and FTIR studies. Fibrillar morphology is evident for the series of solvents, but its dimension (both lateral and diameter) systematically changes with n. Solvent retention power of gels has gradually been increased with increasing n while the thermal degradation of copolymer occurs at same temperature, reflecting varying interactions between copolymer and various aliphatic chain length phthalates in gels. Phase diagrams of the gels exhibit the formation of two kinds of polymer-solvent complexes and have been predicted theoretically through electronic structure calculation. Both the small-angle neutron scattering (SANS) and small-angle X-ray scattering (SAXS) have been performed to elucidate the structure of fibril indicating gradual changes in lamellar organization. The experimental data have been fitted with different models and power law to check their validity. Molecular modeling has been carried out to understand the nature of interaction between copolymer and the solvent through energy minimization program and found a typical n = 6 value of lowest dipolar distance, indicating strongest interaction. The magic number of six has further been explored through quantum chemical calculations. © 2011 American Chemical Society.